Manajemen Keuangan Dalam Meningkatkan Mutu Pendidikan - Yaredi Waruwu; Desi Rahmadani; ella mayasari; Imriani Idrus; Ari Kartiko (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
This research was conducted for the phenomenon of financial management in improving the quality of education at the Boarding School, the purpose of this study was to: find out the financial planning in the madrasa (budgeting) and the implementation of education finance (actuating). This research is a field research using a qualitative approach. The subjects in this study were the Head of Madrasah, Waka Sarana and Infrastructure and Treasurer. Researchers collected data using observation, interviews and documentation. The data analysis used is data reduction, data presentation and data verification. Researchers have a goal to find out how to plan and implement finances in the madrasa so that the madrasa has good financial planning and implementation. The results of this study, firstly, financial planning in improving the quality of education is stated in the form of RKAM which is held every before the new school year begins. Second, the implementation of education finance includes the receipt and expenditure of funds. The funds received at Al Amin come from the BOS Fund, monthly tuition fees and operational funds issued every month. The implementation of financial management in improving the quality of education can be seen in the allocation of funds in the RKAM, namely by the allocation of funds for extracurricular activities, the allocation of funds for facilities and infrastructure at the madrasah by adding facilities, repairs and maintenance.